2012
DOI: 10.1103/physrevd.86.054023
|View full text |Cite
|
Sign up to set email alerts
|

How large can the branching ratio ofBsτ+τbe?

Abstract: Motivated by the large like-sign dimuon charge asymmetry observed recently, whose explanation would require an enhanced decay rate of Bs → τ + τ − , we explore how large a branching ratio of this decay mode is allowed by the present constraints. We use bounds from the lifetimes of B d and Bs, constraints from the branching ratios of related b → sτ + τ − modes, as well as measurements of the mass difference, width difference and CP-violating phase in the Bs-Bs system. Using an effective field theory approach, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…One promising candidate was the decay B s → τ + τ − , which was investigated e.g. in [53,54,55,56,57,58]. Having stronger experimental bounds on this channel would be very helpful, even if the significance of the deviation in the dimuon asymmetry went down recently [59].…”
Section: Introductionmentioning
confidence: 99%
“…One promising candidate was the decay B s → τ + τ − , which was investigated e.g. in [53,54,55,56,57,58]. Having stronger experimental bounds on this channel would be very helpful, even if the significance of the deviation in the dimuon asymmetry went down recently [59].…”
Section: Introductionmentioning
confidence: 99%
“…We observe that as the mass of Z′ boson increases, the contribution of Z′ boson to the branching ratio decreases. For a light Z′ boson with mass = 100 GeV, we find an enhancement up to [20,21] could help to explain the recently observed like-sign dimuon charge asymmetry to some extent. In order to fully reconcile the D0 result, some contributions from NP in the d B sector are needed [79,80].…”
Section: Discussionmentioning
confidence: 74%
“…From Eq. (4), it is clear that the study of [20,21] would explain the observed like-sign dimuon charge asymmetry in the B system. In this paper, we take the mass of Z′ boson in the range of 100 GeV -2 TeV for our calculations.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They do not allow for larger modifications of the decay width difference ∆Γ s of the B s -meson in the SM than 35% assuming single operator dominance. The interplay of several operators allows for larger effects [48].…”
Section: Global Analysismentioning
confidence: 99%